Pemanfaatan Instagram Oleh Komunitas Wisata Grobogan Dalam Mempromosikan Potensi Pariwisata Daerah - Wenday Dwi Novi Kurniawati (Komuniti: Jurnal Komunikasi dan Teknologi Informasi, 2016)
The existence of online community in the field of tourism through social media constructs the new form of developing and operating tourism sector. Social media is used for means of spreading information, communication and promotion. Promoting tourism potential can be carried out easily by these online community. one example of online community in the field of tourism is wisata grobogan community. the objective of this research is to describe the use of instagram done by wisata grobogan community in promoting potential of areas tourism.This research applies qualitative descriptive method. The object of the research is the account of @wisatagrobogan whis is used to promote the potential of areas tourism. Data is collected using semi-structured interview technique.Data analysis method used in this research uses triangulation. The results showed that in the promotion of the tourism potential of the area may go well and smoothly through the four stages, namely the presence of communicators, messaging, media and communicant. And the use of social media Instagram provides many benefits and advantages for Grobogan travel community in promoting the tourism potential of the area. Some of these benefits, among others, can easily disseminate travel information, and can attract the attention of other users more widely supported also by the use of features that are owned Instagram.